Ecological restoration in valley area of semiarid region damaged by shallow buried coal seam mining - Chen Puhao; Wang Jianbin; Wang Haiyan (Open Geosciences)
Coal seams in valley areas are shallow buried, and mining activities have a strong impact on the surface environment, so ecological restoration in this condition is very difficult. Strengthening the monitoring of ecological changes plays an important role in optimizing mining methods and ecological restoration. In this article, a valley area in the northern Shaanxi Province of China was selected as the research area, and a similar ecosystem around the study area was selected as the reference subject. The traditional remote sensing ecological index model was improved, and a new evaluation model was constructed based on the framework of Modified Remote Sensing Ecology index-Deviation from Reference Ecosystem Index-Ecological Restoration Quality Index (ERQI) to study the evolution of the environment in the study area from the perspective of the whole life cycle of mining activities. The results showed that ERQI values in the study area experienced an evolution process from high to low and then gradually increased, reflecting the impact of coal mine production and restoration activities on the environment, in which Burn Area Index and normalized difference vegetation index were more sensitive; after nearly 10 years of restoration, ERQI values in the study area still had a large gap with that of the reference area, some suggestions for improvement of ecological restoration were put forward. The research provided a quantitative approach to describe the evolution of the ecological environment and a scientific basis for the ecological restoration in the mining areas.